Neurosciences and Personal Meanings in the Sense of Identit - Fernández Sixto, Elizabeth (2020)
This review article is based on the identity theory developed from neuroscience. It articulates the physical with the psychic, or the behavior with the environment through social interaction. It consists in admitting the presence of consciousness of brain states in human behavior. Objective. To analyze the identity of the individual associating the brain to thinking and decision-making. Method. A meticulous bibliographic review of the subject was carried out. Scientific articles, journalistic reports and neuroscientific essays of the most recent studies were consulted. It allowed to arrive at a succinct conceptual approach of the subject. Results. Neuroscience has shown that cognitive processes and emotions share neural networks and aim to understand the recognition of the identity of the individual with their emotions. These are functional states of the brain that articulate cognitive aspects such as our sensations. They go through the neural pathway, from the thalamus to the cerebral cortex, through a set of nerve fibers that make the thalamus communicate directly with other components, such as the amygdala. Conclusion. Neuroscience addresses personal meanings of senses of sexual identity in the construction of development of the individual. From prenatal development, through the development of people in childhood and, later, defining their personality in adolescence.